METHOD OF ELIMINATION OF GIARDIASIS INVASION IN CHILDREN - Nurmatova Nargiza Fatxullayevna; Sagdullayeva Mafura Abdukarimovna; Samadov Abduqaxxor Abduraxmonovich; Mallayev Shuxrat Sherqulovich (Web of Journals Publishing, 2025)
Nifuratel, Albendazol and Metronidazol were used in the second step (intervention on parasite and it’s elimination from the host) of 3-step therapy of lambliasis at 125 children.
Keywords: Giardian of infection, antiparasitical preparations, treatment, children.